Food and catering modifications for public health: chronic disease and obesity prevention. (February 2015) - Hankey, Catherine
Abstract Increasing consumption of processed and pre-prepared foods contributes to increased energy and lowered micronutrient intakes. Guidance to assist caterers to prepare products adhering with national and international dietary recommendations is justified and international examples exist. Producing items lower in energy, fat and free sugars may offer health and financial advantages. Consumers are often unaware of the content of meals and labelling of pre-prepared and restaurant meals show promise in improving food choice. Some labelling terms such as 'low fat' may favour increased consumption. Voluntary approaches have led to some product reformulation and portion-size reductions. Mandatory targets are favoured by the health lobby but opposed by industry. Fiscal schemes, including taxes on high fat/sugar foods to alter food intakes, have enjoyed mixed success.